KEUTUHAN DAN KEPADUAN PARAGRAF TULISAN MAHASISWA PROGRAM STUDI PSIKOLOGI FKIK UNIVERSITAS JAMBI - Herman Budiyono (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2014)
This research description aim to unity and coherence paragraph artcle Studies Programme Psychology, Faculty of Medical and Health of Science, University of Jambi. Jambi. This research applies quantitative descriptive method. Population of All these research of student article paragraph, that is 45 paragraphs. From population is taken 50% at random as the sample, gotten 22 paragraphs. Research data is analysed quantitatively, the step: looks for frequency distribution by value " unity and coherence" paragraph; determines classification is frequency distribution based onthe quality; percentage unity and coherence paragraph based on the quality; and presentation of result. Result of research as follows: unity of paragraph with quality very good: 0%; good: 45,5%; enough: 50%; less: 4,5%; and less once: 0% and coherence paragraph with quality very good: 4,5%; good: 63,7%, enough: 22,8%; less: 9%, and less once: 0%. Keywords: unity, coherence, paragraph, article